Antifungal effects of volatile organic compounds produced by Trichoderma koningiopsis T2 against Verticillium dahliae - Kong, Wei-Liang; Ni, Hang; Wang, Wei-Yu; Wu, Xiao-Qin (Frontiers in Microbiology, 2022)
Volatile organic compounds (VOCs) produced by microorganisms are considered promising environmental-safety fumigants for controlling soil-borne diseases. Verticillium dahliae, a notorious fungal pathogen, causes economically important wilt diseases in agriculture and forestry industries. Here, we determined the antifungal activity of VOCs produced by Trichoderma koningiopsis T2. The VOCs from T. koningiopsis T2 were trapped by solid-phase microextraction (SPME) and tentatively identified through gas chromatography–mass spectrometry (GC/MS). The microsclerotia formation, cell wall-degrading enzymes and melanin synthesis of V. dahliae exposed to the VOC mixtures and selected single standards were examined. The results showed that the VOCs produced by strain T2 significantly inhibited the growth of V. dahliae mycelium and reduced the severity of Verticillium wilt in tobacco and cotton. Six individual compounds were identified in the volatilome of T. koningiopsis T2, and the dominant compounds were 3-octanone, 3-methyl-1-butanol, butanoic acid ethyl ester and 2-hexyl-furan. The VOCs of strain T2 exert a significant inhibitory effect on microsclerotia formation and decreased the activities of pectin lyase and endo-β-1,4-glucanase in V. dahliae. VOCs also downregulated the VdT3HR, VdT4HR and VdSCD genes related to melanin synthesis by 29.41-, 10.49-, and 3.11-fold, respectively. Therefore, T. koningiopsis T2 has potential as a promising biofumigant for the biocontrol of Verticillium wilt disease.